Long term effects of antenatal betamethasone on lung function: 30 year follow up of a randomised controlled trial. Issue 8 (6th April 2006) - Dalziel, S R; Rea, H H; Walker, N K; Parag, V; Mantell, C; Rodgers, A; Harding, J E
Abstract : Background: Antenatal betamethasone is routinely used for the prevention of neonatal respiratory distress syndrome in preterm infants. However, little is known of the long term effects of exposure to antenatal betamethasone on lung function in adulthood. Methods: Five hundred and thirty four 30 year olds whose mothers had participated in the first and largest randomised controlled trial of antenatal betamethasone were followed. Lung function was assessed by portable spirometric testing. The prevalence of asthma symptoms was assessed using the European Community Respiratory Health Survey questionnaire. Results: Fifty (20%) betamethasone exposed and 53 (19%) placebo exposed participants met the criteria for current asthma (relative risk 0.98 (95% CI 0.74 to 1.30), p = 0.89). 181 betamethasone exposed and 202 placebo exposed participants had acceptable spirometric data. There were no differences in lung function between betamethasone and placebo exposed groups (mean (SD) forced vital capacity in the betamethasone and placebo groups 105.9 (12.0) v 106.6 (12.6)% predicted, difference = −0.7 (95% CI −3.2 to 1.8), p = 0.59; mean (SD) forced expiratory volume in 1 second in the betamethasone and placebo groups 98.9 (13.4) v 98.5 (13.6)% predicted, difference = 0.3 (95% CI −2.4 to 3.1, p = 0.80)). Conclusions: Antenatal exposure to a single course of betamethasone does not alter lung function or the prevalence of wheeze and asthma at age 30.